Percepção de risco de incêndio em escolas municipais de Campo Magro/PR - Mendes, Celina Milani Rodrigues Amorim (2014)
Evaluate the knowledge and behavior of the school community toward risk of fire is a tool to stimulate the adoption of preventive measures in order to protect the lives and schools property. Check the risk perception that students and teachers from public schools in a city in the metropolitan region of Curitiba have, as well as evaluating the behavior toward a fire and propose solutions, are the purpose of this work. For this visited up 8 public schools in Campo Magro city, Paraná state. Two questionnaires consisting of multiple choice questions related to the perception of fire risk in school and behavior in a fire situation were applied. The first questionnaire was applied in the 3rd year classes (8 years old) and 5th grade (10 years old) of the Elementary School. The second questionnaire was administered to teachers in these classrooms. Altogether we interviewed 16 teachers and 295 students. As a result we have that, students of public schools in elementary school in Campo Magro, do have perception of fire risk in school but are not familiar with the protective measures against fire and how would know the occurrence of a fire at school. Students are also not prepared to act in accordance with the appropriate procedure before any emergency. In comparing students of 3rd and 5th grade, both followed the same pattern of response for most questions, but students of 3rd year, due to lower age, had a lower perception of risk. In the case of teachers of the same school year, although the correct procedure is not clear to all teachers, the majority is aware of the risk of fire in the school and is also familiar with the right procedures to be taken in case of emergency. As a proposal to improve these schools should build a culture of prevention through lectures, discussions in class and including it in the curriculum. It also requires that each school form your school brigade and adopt a program of fire fighting, abandonment plan with regular simulations and basic first aid training. School buildings also need to suit the requirements of the Fire Department, especially in relation to basic security requirements, such as number and correct allocation of fire extinguishers, exchange of overdue charges, emergency signage and emergency lighting.